2014
DOI: 10.3389/fpsyg.2014.00946
|View full text |Cite
|
Sign up to set email alerts
|

Tourette-like behaviors in the normal population are associated with hyperactive/impulsive ADHD-like behaviors but do not relate to deficits in conditioned inhibition or response inhibition

Abstract: Attention-Deficit Hyperactivity Disorder (ADHD) and Tourette Syndrome (TS) present as distinct conditions clinically; however, comorbidity and inhibitory control deficits have been proposed for both. Whilst such deficits have been studied widely within clinical populations, findings are mixed—partly due to comorbidity and/or medication effects—and studies have rarely distinguished between subtypes of the disorders. Studies in the general population are sparse. Using a continuity approach, the present study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Indeed, pure TS may rather be characterized by enhanced executive control (Jackson et al, 2007;Jung et al, 2014) and there is no evidence for automatic inhibitory deficits in TS patients without comorbidity (Ozonoff et al, 1998;Yuen et al, 2005) and independent of medication effects (Kantini et al, 2011). Similar findings were recently shown in relation to TS-like behaviors in the general population when ADHD was controlled for (Heym, Kantini, Checkley & Cassaday, 2014). These findings suggest that TS does not occur in conjunction with deficits in effortful or automatic associative response inhibition.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, pure TS may rather be characterized by enhanced executive control (Jackson et al, 2007;Jung et al, 2014) and there is no evidence for automatic inhibitory deficits in TS patients without comorbidity (Ozonoff et al, 1998;Yuen et al, 2005) and independent of medication effects (Kantini et al, 2011). Similar findings were recently shown in relation to TS-like behaviors in the general population when ADHD was controlled for (Heym, Kantini, Checkley & Cassaday, 2014). These findings suggest that TS does not occur in conjunction with deficits in effortful or automatic associative response inhibition.…”
Section: Introductionsupporting
confidence: 71%
“…Tourette-like behaviors were assessed using the 18-item TS behavior checklist based on frequency occurrence of DSM-IV and ICD10 symptoms for TS (except common complex tics as these would be unlikely in an undiagnosed population) and with a similar question format to the ASRS 1 (Heym et al, 2014). The scale comprises two pure TS subscales: TS-phonic (8 items) related to sounds produced through the nose, mouth or throat (e.g., throat clearing, coughing, sniffing), and TS-motor (7 items) related to unintentional physical movements (e.g., blinking, face twitches, random body movements).…”
Section: Methodsmentioning
confidence: 99%
“…There are few examples in which it has been studied alongside other measures of inhibition (e.g., Stroop Task, Stop-Signal Reaction Time) or in relation to disorders in which inhibition is impaired. Among the studies where conditioned inhibition has been examined there have been reports of weaker conditioned inhibition linked to schizotypy, schizophrenia, and personality disorders (He, Cassaday, Howard, Khalifa, & Bonardi, 2011; He, Cassaday, Park, & Bonardi, 2012; Migo et al, 2006) but no evidence of a link between conditioned inhibition and Tourette’s Syndrome (Heym, Kantini, Checkley, & Cassaday, 2014) nor between conditioned inhibition and behavioral inhibition as measured by the BIS component of the BIS-BAS questionnaire (Carver & White, 1994; He et al, 2013). It is difficult to draw strong conclusions given the number of studies of this kind that currently exists but one lesson from the current research is that a finer grained analysis may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…The two test method to confirm conditioned inhibition (by both summation and retardation tests) has been widely adopted in animal studies, but has been harder to implement in human studies. In human studies, there have been some reports of conditioned inhibition confirmed by summation test ( He et al, 2013 ; Heym et al, 2014 ; Thurston and Cassaday, 2015 ) but these have been relatively few ( Sosa and dos Santos, 2019 ; Sosa and Ramίrez, 2019 ). Indeed, it has been argued that studies of feature negative inhibitory discrimination learning of the kind typically used to successfully demonstrate conditioned inhibition, but which do not include (or do not subsequently pass) the formal tests to confirm conditioned inhibition should also be considered ( Sosa and dos Santos, 2019 ; Sosa and Ramίrez, 2019 ).…”
Section: Introductionmentioning
confidence: 99%